PENGARUH PROMOSI DAN STOK BARANG TERHADAP VOLUME PENJUALAN PADA CV. KALIMANTAN INDAH PERKASA DI MEDAN - Annisa Balqis, Nur; Antoro, Budi; Harahap, Ahmad Taufiq (PT. ANAN PUBLISHER CENDEKIA, 2025)
This research aims to examine the influence of promotion and inventory on sales volume at CV. Kalimantan Indah Perkasa in Medan. Promotion and inventory availability are crucial marketing strategies that significantly impact consumer purchasing decisions and company performance. This study uses a quantitative approach with multiple linear regression analysis. Data were obtained through questionnaires distributed to 95 respondents. The results showed that both promotion and inventory had a significant and simultaneous effect on sales volume, with a determination coefficient of 76.5%. These findings suggest that an integrated strategy involving effective promotion and optimal inventory management is essential to improve sales performance in distribution companies. The implication of this research highlights the importance of synchronization between marketing communication and operational readiness in achieving company targets.